1993
DOI: 10.1212/wnl.43.12.2652
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of mutations in the gene for type III collagen (COL3A1) as a common cause of intracranial aneurysms or cervical artery dissections

Abstract: We performed detailed DNA sequencing analysis on type III collagen cDNA from 58 patients with either intracranial artery aneurysms or cervical artery dissections. The 58 patients were of seven different nationalities; among the patients were three pairs of relatives, so that 55 were unrelated, and of these, 29 had at least one blood relative with either an intracranial artery aneurysm or a cervical artery dissection. The age of the patients at the time of diagnosis ranged from 15 to 68 years (mean +/- SD = 40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(54 citation statements)
references
References 0 publications
4
50
0
Order By: Relevance
“…2 This type of mutation (glycine substitutions in triple helical region of COL3A1) is typical for EDS-IV, but was not found in CAD patients without clinical signs of vascular EDS. 14,30 Our findings in family I suggested that a patient with familial CAD might be affected with mild and otherwise unrecognized forms of vascular EDS.…”
Section: Martin Et Al Familial Cervical Artery Dissections 2927mentioning
confidence: 81%
“…2 This type of mutation (glycine substitutions in triple helical region of COL3A1) is typical for EDS-IV, but was not found in CAD patients without clinical signs of vascular EDS. 14,30 Our findings in family I suggested that a patient with familial CAD might be affected with mild and otherwise unrecognized forms of vascular EDS.…”
Section: Martin Et Al Familial Cervical Artery Dissections 2927mentioning
confidence: 81%
“…34,35 There is also accumulating evidence indicating that overdegradation of vascular structural proteins by proteinases is an important mechanism involved in the development and rupture of aneurysms. 7 The present study sought to ascertain whether polymorphisms in MMP genes influence the susceptibility of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Analyses of the connective tissue in walls of IA documented anomalies in the type III collagen network 19 -22 but found no mutations in the COL3A1 gene itself. 23,24 Although IA families have been collected in several countries, a sufficient number of large pedigrees for classical linkage studies has not been recruited so far. Recently, 83 affected Japanese sib pairs were genotyped with microsatellite polymorphisms at 404 chromosomal loci by Onda et al 25 They found 3 suggestive linkages for IA on chromosomes 5q22 to 31, 14q22, and-with the highest logarithm of odds score-7q11.…”
mentioning
confidence: 99%